2018
DOI: 10.1002/pssa.201700997
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Power Factor in Nanostructured Materials With Randomized Nanoinclusions

Abstract: Here, the electric and thermoelectric transport coefficients of nanocomposites are investigated using the Non-Equilibrium Green's Function (NEGF) method, which can accurately capture the details of geometry and disorder in these structures. Two-dimensional (2D) channels with embedded nanoinclusions (NIs) are considered, which are modelled as potential barriers of cylindrical shape and height V B . The effect of randomness of the NIs on the thermoelectric power factor is investigated by varying the positions, d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

5
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…We simulate a dense, hexagonally oriented network, in order to maximize its effect on transport properties. Whether the network is regular or randomized, makes only little difference to the PF [196]. Potential barriers formed by NIs, similar to those formed in SLs or by grain boundaries, could be expected to also provide energy filtering and improve the Seebeck coefficient, and hopefully the PF [197,198].…”
Section: Nanoinclusions Voids and The Power Factormentioning
confidence: 99%
See 2 more Smart Citations
“…We simulate a dense, hexagonally oriented network, in order to maximize its effect on transport properties. Whether the network is regular or randomized, makes only little difference to the PF [196]. Potential barriers formed by NIs, similar to those formed in SLs or by grain boundaries, could be expected to also provide energy filtering and improve the Seebeck coefficient, and hopefully the PF [197,198].…”
Section: Nanoinclusions Voids and The Power Factormentioning
confidence: 99%
“…What is detrimental are variations in the barrier heights (that degrade the conductivity) and extremely thin, easy to tunnel barriers (which degrade the Seebeck coefficient) [69,180]. In the case of NIs, in a similar manner the variability in the geometry and positions of the NIs does not affect the power factor in a noticeable manner [196], but also for low V B the density and V B itself do not affect it either.…”
Section: Nanoinclusions Voids and The Power Factormentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, we note that recent theoretical studies about the effect of the effect of variations for electronic transport (where the mean-free-path is much shorted), is not as noticeable. 6,94 Thus, variability can be used as means to achieve lower thermal conductivity without affecting the electronic system, which could be advantageous for thermoelectric applications.…”
Section: Analytical Models -Extensions and Validationmentioning
confidence: 99%
“…More recent studies, reported in the p-type Pb0.98Na0.02Te-SrTe system an extremely low κ of 0.5 W K −1 m −1 and a ZT of 2.5 at 923K [13], and a similarly low κ = 0.55 W K −1 m −1 in a SiGe nanoporous system [7]. Moreover, our prior works also point out that hierarchical nanostructures can improve the thermoelectric power factor as well [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%